Câteva considerații asupra receptării protocronismului românesc - Vlad-Ion Pappu (Revista de Istorie și Teorie Literară)
The present paper represents a remake, on a wider scale, but far from being exhaustive, of the problem of Protochronism, as originally thought by Edgar Papu (1908-1993), her creator. The same problem was widely debated by the author of this work, Vlad-Ion Pappu, in the literary file Edgar Papu and Protochronism in the space of the “Luceafărul” magazine, Eikon Publishing House, Cluj, 2016. The occasion for this academic recurrence was the celebration of a quarter century after Edgar Papu’s extinction, as well as the recent occurrence of a new contribution to the theme in the monumental synthesis elaborated by Acad. Eugen Simion, Posterity of Eugen Lovinescu, Tracus Arte Publishing House, Bucharest, 2017. Conceived tripartite, the current considerations examine the reception of the work History of Modern Romanian Civilization (1924–1925) by Eug. Lovinescu in the interwar critique, present the landmarks that unified Edgar Papu’s vision of Romanian literature, emphasizing the homogeneity of his judgments from the interwar period (1932) to the post-December period (1991), as well as the critical texts with which his book Out of our Classical Writers. Contributions to the Idea of a Romanian Protochronism (1977, 1989, as well as the version published in the review “Românul”, March-July 1991) was approached. In the last section were analyzed some of the sociological and politological theses on nationalism, which struck the perception of Protochronism after 1989. There were revealed the mechanism and the ideological motivations through which E. Papu’s Protochronism was mystified and subjected to a Stalinist political process, confusing his entire critical reception, as well as how his idea was recovered by national communism to be propagandistically exploited.